Die theologischen Fragmente - Asterius, the Sophist, -approximately 341. (Vigiliae Christianae, Supplements, 1993)
This volume is the first critical edition of the theological fragments of Asterius of Cappadocia, the so-called Arian Sophist, who lived in the early fourth century. The first part of the volume provides an introduction to the theological thought of Asterius, an important member of the \'Eusebians\'. It also compares the theological thought of Asterius with Origen's and Arius' theology. The second part consists of the 77 theological fragments of Asterius of Cappadocia with a German translation. In the third part a commentary is given for each fragment explaining the content, the language and also the authenticity of the texts.